Philosophical and Modern Scientific Revival of John Duns Scotus in Defense of Principle of Causality - Roshlan Rahman Dipto; Md. Iftakhar Hossain Simanto (HISTORICAL: Journal of History and Social Sciences, 2026)
In this paper, the causal principle, "whatever begins to exist has a cause" is defended  by resurrecting the medieval philosopher John Duns Scotus's argument for God's existence. In light of recent criticisms from philosophers and new atheists who question the universality of causality by pointing to uncaused beginnings and quantum indeterminacy, we reconcile Scotus's modal-metaphysical framework with contemporary philosophy and physics. In support of the causal principle, a thorough analysis of the premises has been presented. We also provide a scientific and philosophical case against limitless causal regresses. By integrating modern empirical natural philosophy with medieval natural theology, the synthesis reaffirms the causal principle's relevancy in modern time and attempts to refute arguments against God's existence as First Cause based upon attacking the causal principle.